Photocatalytic property of polyaniline-TiO2-Fe3O4 nanocomposites for photodegradation of reactive black 5 DYES / Nur Aziera Jumat - Nur Aziera , Jumat (2019)

(untitled)
Textile industry produces a lot of carcinogenic and toxic dyes especially RB5 dyes that can cause serious environmental problem. Among all wastewater treatment, photocatalysis is the most effective and practical techniques because it degrades pollutant to harmless substances and use natural sunlight or artificial illumination. Nowadays, ternary nanocomposites catalyst has been extensively investigated for photocatalytic degradation of organic pollutant. In this study, ternary catalyst of PAni-TiO2-Fe3O4 nanocomposite was newly designed and has been evaluated for photodegradation of RB5 dyes. A series of PAni-TiO2 (wt% of TiO2 = 5%, 10%, 20% and 40%) and PAni-TiO2-Fe3O4 (wt% of Fe3O4 = 5%, 10% and 20%) were synthesized via the chemical oxidative polymerization. The chemical structure of PAni nanocomposites were confirmed by Fourier transformed infra-red (FTIR), ultraviolet-visible (UV-Vis) and X-ray diffractometry (XRD) analyses. The electrical conductivity was examined by four probe point while the morphological study was investigated by FESEM. Various catalyst such as, TiO2, Fe3O4, PAni, PAni-TiO2, PAni-Fe3O4 and PAni-TiO2-Fe3O4 were used in photocatalytic degradation of RB5 for 2 hours under Xenon light irradiation with filter light below 380 nm. Result obtained showed that, PAni-TiO2-Fe3O4(10%) demonstrated the highest photocatalytic activity with 85.3% photodegradation. Therefore, further study for the effect of reaction condition (adsorption time, reaction time, initial dye concentration and amount of catalyst) was focused on PAni-TiO2-Fe3O4. It was found that PAni-TiO2-Fe3O4 performed best in photodegradation activity under reaction conditions of 1 hour adsorption time, 3 hours reaction time, 10 ppm initial dye concentration and 15 mg amount of catalyst. All catalysts were further photodegraded under the same condition in order to obtain the kinetic plot. The photodegradation process is followed the pseudo first order reaction, and the calculated rate constant, k followed the trend of: PAni-TiO2-Fe3O4(10%) (0.0159 min-1) > PAni-Fe3O4 (0.0103 min-1) > PAni-TiO2 (0.0068 min-1) > PAni (0.0059 min-1) > TiO2 (0.0008 min-1). The photocatalytic properties of nanocomposites were analyzed by its e--h+ recombination and band gap using photoluminescence (PL) spectra and band gap from Tauc plot, respectively. The presence of Fe3O4 in the nanocomposites has greatly inhibited the e--h+ pair recombination which agrees well with the PL spectra. Furthermore, the band gap of PAni-TiO2-Fe3O4(10%) from the Tauc plot was 1.50 eV which achieved the target to absorb most of the visible light spectrum. In conclusion, the best ternary catalyst that synthesized here (PAni-TiO2-Fe3O4) is a potential catalyst that exhibit excellent photocatalytic activity with 94.4% photodegradation of RB5 dyes by using a low cost system (250 mg/L catalyst; visible light irradiation) compared to TiO2-CdS catalyst with ≈ 94% photodegradation of RB5 dyes but need high cost system (1000 mg/L catalyst; ultrasonic irradiation) from previous study.